Occupational Competitiveness Analysis of the U.S. Transportation and Logistics Cluster. Issue 1 (January 2020) - Kumar, Indraneel; Beaulieu, Lionel J.; Zhalnin, Andrey; Song, Chun
This paper explores occupational or human capital attributes of transportation and logistics clusters in the U.S., by analyzing logistics clusters, such as Memphis and uncovers the differences in occupations or knowledge and skill contents of the workforce. The research builds on previous studies funded by the U.S. Economic Development Administration on U.S. occupation clusters providing insights on logistics clusters from a human capital perspective. The study draws specifically from the industry-and-occupation cluster crosswalks building on previous research on occupation cluster industry cluster-location quotient (OCIC-LQ), and recent research on computerization and automation of occupations. The research questions include how knowledge occupation clusters differ in specialization within the select logistics clusters. How can occupation clusters inform the traditional cluster-based economic development policies in the U.S.? How might automation impact the logistics cluster? The findings show that transportation and logistics clusters are unique in knowledge-based occupations with some commonalities found in different locations. Based on occupational and staffing patterns, nearly 71% of occupations or tasks and activities within the transportation and logistics cluster in Memphis is at risk of automation. The research builds a case for place-based cluster development and people-based workforce development for transportation and logistics cluster in the U.S.